2020
DOI: 10.3390/vaccines8020155
|View full text |Cite
|
Sign up to set email alerts
|

Response Type and Host Species may be Sufficient to Predict Dose-Response Curve Shape for Adenoviral Vector Vaccines

Abstract: Vaccine dose-response curves can follow both saturating and peaking shapes. Dose-response curves for adenoviral vector vaccines have not been systematically described. In this paper, we explore the dose-response shape of published adenoviral animal and human studies. Where data were informative, dose-response was approximately five times more likely to be peaking than saturating. There was evidence that host species and response type may be sufficient for prediction of dose-response curve shape. Dose-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This is likely the result of using too few doses or not dosing at a sufficiently large dose to observe peaking or saturating dose-response behaviour. We have previously shown that curve shape could not be determined for 75% of adenoviral dose-response data [ 8 ]. However, in this case, it is possible that dosing at a large enough magnitude to determine curve shape could cause an unacceptable number of grade 3+ adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely the result of using too few doses or not dosing at a sufficiently large dose to observe peaking or saturating dose-response behaviour. We have previously shown that curve shape could not be determined for 75% of adenoviral dose-response data [ 8 ]. However, in this case, it is possible that dosing at a large enough magnitude to determine curve shape could cause an unacceptable number of grade 3+ adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…We also calibrated a representative non-saturating (“peaking”) curve, using the methods discussed in [ 8 ]. However, as these methods did not support the non-saturating curve providing a better description of the data, we assume that the dose-response follows a sigmoidal function ( Supplementary S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas for many drugs, we can assume that an increased dose increases efficacy, for vaccines, this may not be the case. It is possible that there exists some dose for which the probability of efficacy is maximised and that increasing this dose decreases the probability of efficacious response [ 3 , 24 , 25 , 26 ]. Below, we define approaches for modelling vaccine efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we have launched the novel field of vaccine ‘Immunostimulation/Immunodynamic’ (IS/ID) modelling, an adaptation of methods used in drug development to systematically and quantitatively identify ‘best’ dose. We have shown its potential in a novel TB vaccine [14] , [15] and Adenoviral-based vaccines [16] , [17] , [18] and IS/ID modelling has been recognised by vaccine developers and modellers as the future methodology to optimise vaccine development [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%